Evaluation of Ambient PM2.5 Levels in The Campus Area Using Information from A Low-Cost Sensor Device - Dian Hudawan Santoso; Ahmad Yuda Hermawan; Bryan Tegar Mahardika; Ichlasul Kevin Hilmi; Mufid Rona Nuansa (Yayasan Literasi Sains Indonesia, 2025)
This study assesses ambient PM2.5 concentrations alongside temperature and humidity at two campus sites, UPN and UGM, utilising a Low-Cost Sensor (LCS) IoT-based device. LCS-IoT provides a cost-effective and sustainable solution for air quality monitoring, addressing the shortcomings of costly traditional sensors. Data indicates considerable daily fluctuations in PM2.5 concentrations; UPN documented morning peaks surpassing 100 µg/m³ at approximately 08:00 AM, but UGM exhibited lower peaks, remaining below 45 µg/m³ during the same timeframe. This discrepancy is associated with the positioning of UGM's sensors within the campus's Green Open Space (RTH)/vegetation zone, whereas UPN is situated adjacent to a bustling roadway. This observation highlights the effectiveness of green spaces and vegetation in reducing PM2.5 pollution. The temperature trend at both analogue locations peaked at 31-33°C during the day. Relative humidity exhibits an inverse correlation with temperature, peaking at 80-90% during the early morning and declining to a low of 59-70% during the day. The research findings underscore the significance of air quality monitoring within the campus environment and the necessity for specific mitigation strategies to safeguard the health of the academic community. Extended research with prolonged measuring periods is recommended for a more thorough comprehension.